Harry W. Richardson. Urban economics. Inglaterra : Penguin, 1971. 208 p. - Ruiz Chiapetto, Crescencio (Estudios Demográficos y Urbanos, 1972)
HARRY W. RICHARDSON, Urban Economics, Inglaterra, Penguin, 1971.